Folding of Aquaporin 1: Multiple evidence that helix 3 can shift out of the membrane core. (14th May 2014) - Virkki, Minttu T.; Agrawal, Nitin; Edsbäcker, Elin; Cristobal, Susana; Elofsson, Arne; Kauko, Anni
Abstract: The folding of most integral membrane proteins follows a two‐step process: initially, individual transmembrane helices are inserted into the membrane by the Sec translocon. Thereafter, these helices fold to shape the final conformation of the protein. However, for some proteins, including Aquaporin 1 (AQP1), the folding appears to follow a more complicated path. AQP1 has been reported to first insert as a four‐helical intermediate, where helix 2 and 4 are not inserted into the membrane. In a second step, this intermediate is folded into a six‐helical topology. During this process, the orientation of the third helix is inverted. Here, we propose a mechanism for how this reorientation could be initiated: first, helix 3 slides out from the membrane core resulting in that the preceding loop enters the membrane. The final conformation could then be formed as helix 2, 3, and 4 are inserted into the membrane and the reentrant regions come together. We find support for the first step in this process by showing that the loop preceding helix 3 can insert into the membrane. Further, hydrophobicity curves, experimentally measured insertion efficiencies and MD‐simulations suggest that the barrier between these two hydrophobic regions is relatively low, supporting the idea that helix 3 can slide out of the membrane core, initiating the rearrangement process.